2019
DOI: 10.1038/s41401-019-0254-4
|View full text |Cite
|
Sign up to set email alerts
|

3-Deoxy-2β,16-dihydroxynagilactone E, a natural compound from Podocarpus nagi, preferentially inhibits JAK2/STAT3 signaling by allosterically interacting with the regulatory domain of JAK2 and induces apoptosis of cancer cells

Abstract: The Janus kinase (JAK)/signal transducer and activator of transcription (STAT) pathways, especially the JAK2/STAT3 pathway, play vital roles in the development of many malignancies. Overactivation of STAT3 promotes cancer cell survival and proliferation. Therefore, the JAK2/STAT3-signaling pathway has been considered a promising target for cancer therapy. In this study, we identified a natural compound 3-deoxy-2β,16-dihydroxynagilactone E (B6) from the traditional Chinese medicinal plant Podocarpus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Activated JAK2 phosphorylates STAT3, leading to its nuclear translocation and tumorigenesis [ 35 ]. A recent study showed that the natural compound B6 (3-deoxy-2 β ,16-dihydroxynagilactone E) inhibits the phosphorylation of STAT3 by inactivating and interacting with JAK2, thereby inhibiting growth and inducing apoptosis of breast cancer cells with overactivated STAT3; this provides a novel promising strategy for the treatment of cancers with JAK2/STAT3 overactivation [ 36 ]. A Japanese study found that p-STAT3 expression was correlated with OS, and the activation of the JAK2/STAT3 pathway is critical for the survival of clear-cell ovarian cancers [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Activated JAK2 phosphorylates STAT3, leading to its nuclear translocation and tumorigenesis [ 35 ]. A recent study showed that the natural compound B6 (3-deoxy-2 β ,16-dihydroxynagilactone E) inhibits the phosphorylation of STAT3 by inactivating and interacting with JAK2, thereby inhibiting growth and inducing apoptosis of breast cancer cells with overactivated STAT3; this provides a novel promising strategy for the treatment of cancers with JAK2/STAT3 overactivation [ 36 ]. A Japanese study found that p-STAT3 expression was correlated with OS, and the activation of the JAK2/STAT3 pathway is critical for the survival of clear-cell ovarian cancers [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this compound does not classically bind to the kinase pocket of the enzyme, as it is frequently the case with small molecule inhibitors, but it was found to interact with the noncatalytic FERM-SH2 domain of JAK2. In doing so, B6 preferentially inhibits the growth of cancer cells with overactivated STAT3, like the MDA-MB-231 and MDA-MB-468 breast cancer cell lines, both potently engaged toward apoptosis under treatment with the Nag-E derivative [31].…”
Section: Tgf-e1mentioning
confidence: 99%
“…The derivative 3-deoxy-2β-hydroxy-nagilactone E (Fig. 4 ) is also a potent inhibitor of cancer cell growth, 3-to-8-fold more active than its derivative 3-deoxy-2β,16-dihydroxy-nagilactone E (designated B6, [ 31 ]) against different cancer cell lines, and much more potent than its glycoside derivative 16-O-β- d -glucopyranosyl-nagilactone E which is totally inactive in vitro [ 15 ]. Preliminary structure–activity relationships can be defined in the Nag-E series.…”
Section: Anticancer Activities Of Nagilactonesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that phosphorylated STAT3 expression is associated with survival and mammographic density of breast cancer patients . Moreover, various natural compounds, including 3‐deoxy‐2 β ,16‐dihydroxynagilactone E, apigenin, genistein, inhibit STAT3 signaling and induce apoptosis in cancer cells . Therefore, proteins in pathways that are altered during the process of mammary tumorigenesis may be promising targets of future chemopreventive drugs .…”
Section: Resultsmentioning
confidence: 99%